2012
DOI: 10.2478/s11535-012-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylcholine on Characeae K+ channels at rest and during action potential generation

Abstract: The role of acetylcholine (ACh) as a signalling molecule in plants was investigated using a model system of Characeae cells. The effect of ACh on conductance of K+ channels in Nitella flexilis cells and on the action potential generation in Nitellopsis obtusa cells after H+-ATPase inhibition, where repolarization occurs after the opening of outward rectifying K+ channels, was investigated. Voltage-clamp method based on only one electrode impalement was used to evaluate the activity of separate potassium ion tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Species without cortex and long internodes such as Nitellopsis obtusa and Nitella translucens were cultured for physiological experiments, either in outdoor ponds or (more frequently) in the laboratory, but growth rates were not published for such cultures. Nitellopsis obtusa was transferred from the field to aquaria with tape water or site water in room temperature and under lamps and thus kept alive until the start of the experiments (Kurtyka et al, 2011 [ 171 ], Kisnieriene et al, 2012 [ 172 ]). In a laboratory of the University of Valencia, Spain, a number of charophyte species are kept in culture in small pots containing a sand/sediment substrate mixture, which are placed in larger beakers with tape water (Rodrigo et al, 2017 [ 170 ], Rodrigo 2021 [ 84 ]).…”
Section: Transplantations Of Threatened Charophytesmentioning
confidence: 99%
“…Species without cortex and long internodes such as Nitellopsis obtusa and Nitella translucens were cultured for physiological experiments, either in outdoor ponds or (more frequently) in the laboratory, but growth rates were not published for such cultures. Nitellopsis obtusa was transferred from the field to aquaria with tape water or site water in room temperature and under lamps and thus kept alive until the start of the experiments (Kurtyka et al, 2011 [ 171 ], Kisnieriene et al, 2012 [ 172 ]). In a laboratory of the University of Valencia, Spain, a number of charophyte species are kept in culture in small pots containing a sand/sediment substrate mixture, which are placed in larger beakers with tape water (Rodrigo et al, 2017 [ 170 ], Rodrigo 2021 [ 84 ]).…”
Section: Transplantations Of Threatened Charophytesmentioning
confidence: 99%
“…Thus, changes in membrane potential can be used to reveal the instantaneous effect of many chemicals on the activity of plant membrane ion transport systems determining rest potential. For example we found that 1 mM acetylcholine (a classical neurotransmitter) has depolarising effect on the resting potential of N. obtusa cells (by 12.2 AE 2.1 mV from -225.3 AE 5.6 mV) and causes a significant increase in membrane permeability (22.5%, P < 0.002, n = 10) (Kisnieriene et al 2012).…”
Section: Membrane Potential As An Indicator Of Early Effect Of Bioactmentioning
confidence: 82%
“…To measure the velocity of AP repolarisation we differentiated 50 s periods starting from the peak of AP. The highest value of dE/dt was taken to evaluate prolongation of repolarisation (Kisnieriene et al 2012). For example, we compared pattern of single action potentials in APW and 5 mM ACh solutions.…”
Section: Action Potential Pattern As a Biomarker Of Bc Effects On Memmentioning
confidence: 99%
See 1 more Smart Citation
“…APW artificial pond water (control solution), APW2 APW after Ni 2+ treatment, AP action potential and duration of action potential in plant cells (Volkov and Ranatunga 2006). Both types of K + channels-inward rectifying and outward rectifying, are known to show strong voltage dependence (Kisnieriene et al 2012). Inward-rectified channels are open only at hyperpolarizing membrane potentials whereas the outward rectifiers are open when the plant cell membrane is depolarized from the typical membrane potential.…”
Section: Discussionmentioning
confidence: 99%